Pendampingan Pemasaran Produk UMKM Keripik Sale Pisang Kowang Senepo Ponorogo melalui Pemanfaatan Media Sosial - Al Manaanu, Yusuf; Munawaroh , Hifdhotul; Naufaldi, Ahmad; Muchyiddin, Abdillah Khayyi; Rabbani, Fahrian Akbar; Hafidzh , Abdilah; Mulyono , Puji; Abdi, Zahidan Kafabillah; Ar-rijal, Mohammad Nasril Anwar; Abshor, Faiq Ubaidillah Ulil; Wijaya, Riva Angga; Ramdani, Ikhsan; Harun, Moh. (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This community engagement program aimed to provide assistance to local MSME actors in marketing banana chips products through social media in Dukuh Kowang, Senepo Village, Slahung District, Ponorogo. The activities included training on digital marketing theory, practical sessions on creating engaging content, and advertising strategies. The implementation method involved needs assessment surveys, planning, hands-on training, and monitoring. Evaluation results showed increased participants' understanding and improved digital skills. Social media followers grew by 24% on TikTok. This program differs from similar initiatives by applying a participatory approach and contextual strategies suited to rural areas. Practical implications include increased confidence among MSME actors in marketing their products digitally and the establishment of sustainable marketing patterns. The program also opens up opportunities for enhancing the local economy. However, challenges such as low digital literacy and limited technological access remain. Continued support and follow-up mentoring are necessary to ensure that the MSMEs can continue to grow independently.